Effects of Using Benzalkonium Chloride (BZK) Disinfectant Against Density and Compressive Strength of Concrete - Hari Prasetiyo; Agung Sumarno (NAROTAMA UNIVERSITY, Indonesia, 2021)
During the Covid-19 pandemic, where’s the number of infections was increasing every day, there were many uses of massive disinfectants as a means of suppressing the spread of viruses in the environment. No exception, buildings, structures, and residential areas are also exposed to disinfectants every day to avoid and kill the growth of invisible viruses around us. The use of chemical disinfectants such as Benzalkonium Chloride contained on floor cleaning products is often used by the public and even disinfection officers because they are easy to get. The purpose of this study was to determine the disinfectant effect of Benzalkonium Chloride with the recommended level of disinfection dissolving spray and soak (penetration) on the density and compressive strength of concrete. The method used in this research was experimental by conducting trial mixes and special treatments that are carried out at the Becakayu Toll Road Concrete Batching Plant Laboratory - PT. Waskita Beton Precast, Tbk. From the results of the study, it was concluded that the decrease in density in the concrete with Benzalkonium Chloride spray treatment and normal water spray had an average density decrease and the concrete with Benzalkonium Chloride spray had a higher reduction value than that of water spray treatment, whereas in the samples the penetration treatment of Benzalkonium Chloride and normal water curing had an average density increase and the penetration treatment of Benzalkonium Chloride had a higher density value than that of normal water curing concrete. For the results of the compressive strength of the test objects at all qualities (K-175, K-300, and K-500), Benzalkonium Chloride spray treatment and water spray experienced an increase in compressive strength at the age of 14 days but the compressive strength decreased again at the age of 28 days, whereas the benzalkonium Chloride spray treatment sample on average has a lower compressive strength than the water sprayed test sample.